Influence of family financial socialization on academic success in college - Sabri, Mohamad Fazli; Gudmunson, Clinton G.; Griesdorn, Timothy S.; Dean, Lukas R. (Springer Publishing Company, 2020)
Explicit parent–child financial socialization is one way that parents may help children feel less stress in college and increase their academic performance. To test this assumption, we used family financial socialization theory to inform multivariate analysis of variance (MANOVA) and structural equation models (SEM). The results largely support the theory. Participants were 752 college students from a U.S. university. Specific findings indicate that students from more affluent families were more often taught to budget. Parent–child teaching/training was strongly associated with felt parental–financial influence and fewer worrisome academic behaviors because of economic pressure. Students who felt greater parent–financial influence and experienced fewer effects of economic pressure, achieved higher college grade point averages (GPAs). An implication of this study is the importance of strengthening support for financial learning in families.